1992
DOI: 10.1039/an9921700031
|View full text |Cite
|
Sign up to set email alerts
|

Determination of lead in wines by hydride generation atomic absorption spectrometry

Abstract: The optimization of lead hydride generation in aqueous ethanolic media and the influence on its generation of the wine components, both white and red, have been studied. These interferences were overcome by careful control of the parameters affecting hydride generation and the procedure was applied to the determination of Pb in wines. The method is fast, accurate and sensitive and can be used to quantify 24 ppb of Pb in wines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
1
11
1
Order By: Relevance
“…No significant effects were observed from ethanol (up to almost 100%), potassium tartrate (up to 1%, m/v) and dextrose (up to 5%, m/v) on the generation of lead hydride and consequently the absorbance. The results for ethanol were different from that reported by Cacho et al [25], who observed interference from ethanol using H 2 O 2 as oxidizing agent in analysis of wine samples for lead. This was probably due to the differences in the performance of the oxidizing agents, K 3 Fe(CN) 6 and H 2 O 2 , used to convert P(II) to Pb(IV).…”
Section: Effects Of Major Components In Winecontrasting
confidence: 99%
See 3 more Smart Citations
“…No significant effects were observed from ethanol (up to almost 100%), potassium tartrate (up to 1%, m/v) and dextrose (up to 5%, m/v) on the generation of lead hydride and consequently the absorbance. The results for ethanol were different from that reported by Cacho et al [25], who observed interference from ethanol using H 2 O 2 as oxidizing agent in analysis of wine samples for lead. This was probably due to the differences in the performance of the oxidizing agents, K 3 Fe(CN) 6 and H 2 O 2 , used to convert P(II) to Pb(IV).…”
Section: Effects Of Major Components In Winecontrasting
confidence: 99%
“…The reduction in the signal profile was similar to that observed with HCl concentration greater than 0.4% (v/v). When compared with potassium tartrate, the suppression or decrease in hydride generation efficiency with tartaric acid was attributed to the increased acidity of the sample solution as also reported in a previous work [25].…”
Section: Effects Of Major Components In Winesupporting
confidence: 76%
See 2 more Smart Citations
“…1,[19][20][21] However, for wine samples' analysis, ethanol matrix markedly suppresses the efficiency of lead hydride generation, 22 which calls for the development of simple on-line preconcentration and separation procedures. To date, such work dealing with the combination of flow injection/sequential injection on-line preconcentration and separation with hydride generation atomic fluorescence spectrometry (HG-AFS) is rare, 2 due to the narrow range of acidity required for the generation of lead hydride.…”
Section: Matricesmentioning
confidence: 99%